External quality assessment of reading and interpretation of malaria rapid diagnostic tests among 1849 end-users in the Democratic Republic of the Congo through Short Message Service (SMS). - Pierre Mukadi (Public Library of Science (PLoS), 2013)
Background Although malaria rapid diagnostic tests (RDT) are simple to perform, they remain subject to errors, mainly related to the post-analytical phase. We organized the first large scale SMS based external quality assessment (EQA) on correct reading and interpretation of photographs of a three-band malaria RDT among laboratory health workers in the Democratic Republic of the Congo (DR Congo). Methods and findings High resolution EQA photographs of 10 RDT results together with a questionnaire were distributed to health facilities in 9 out of 11 provinces in DR Congo. Each laboratory health worker answered the EQA by Short Message Service (SMS). Filled-in questionnaires from each health facility were sent back to Kinshasa. A total of 1849 laboratory health workers in 1014 health facilities participated. Most frequent errors in RDT reading were i) failure to recognize invalid (13.2-32.5% ) or negative test results (9.8-12.8%), (ii) overlooking faint test lines (4.1-31.2%) and (iii) incorrect identification of the malaria species (12.1-17.4%). No uniform strategy for diagnosis of malaria at the health facility was present. Stock outs of RDTs occurred frequently. Half of the health facilities had not received an RDT training. Only two thirds used the RDT recommended by the National Malaria Control Program. Performance of RDT reading was positively associated with training and the technical level of health facility. Facilities with RDT positivity rates >50% and located in Eastern DR Congo performed worse. Conclusions Our study confirmed that errors in reading and interpretation of malaria RDTs are widespread and highlighted the problem of stock outs of RDTs. Adequate training of end-users in the application of malaria RDTs associated with regular EQAs is recommended.